Does Corn Market Uncertainty Impact the US Ethanol Prices? - Dutta, Anupam; Bouri, Elie; Junttila, Juha; Uddin, Gazi Salah (Wiley Open Access, 2018)
The growing interest in biofuel as a green energy source has intensified the linkages between corn and ethanol markets, especially in the United States that represents the largest producing and exporting country for ethanol in the world. In this study, we examine the effect of corn market uncertainty on the price changes of US ethanol applying a set of GARCH-jump models. We find that the US ethanol price changes react positively to the corn market volatility shocks after controlling for the effect of oil price uncertainty. In addition, we document that the impact of corn price volatility on the US ethanol prices appears to be asymmetric. Specifically, only the positive corn market volatility shocks are found to influence the ethanol market returns. Our findings also suggest that time-varying jumps do exist in the ethanol market.
Keywords: corn price uncertainty; GARCH–jump model; oil price volatility; US ethanol market; volatility shocks; asymmetry; prices